The Similarity Measurement of Human DNA Profile Using Fuzzy Similarity - Meira Parma Dewi; Nurtami Soedarsono (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2020)
This research investigated the similarity of human DNA profile using fuzzy similarity measure. The similarity measurement of DNA profile had been done by measuring the similarity between query’s DNA profile and its biological family such as father, mother, brother, sister, grandmother and grandfather. The similarity measurement had been done to the short tandem repeat (STR) alleles in sixteen loci. The result of the experiment showed that each simulation gave matching result. This research is useful for Indonesian National Police (POLRI) in identifying process of disaster victim, terrorism victim and other criminal conduct.